2014
DOI: 10.2174/1570162x12666140207161000
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Comparison of Enteroaggregative Escherichia coli Isolates from HIV-Positive and Non-HIV Diarrheal Samples

Abstract: Enteroaggregative Escherichia coli (EAEC) have been isolated from both HIV-positive and non-HIV diarrheal samples. In this study a collection of 18 isolates from these two groups were compared for biofilm formation and antibiotic resistance and for the presence of 14 virulence-related genes. All the HIV-positive and over 66% of the non- HIV strains were PCR-negative for adhesion-related sequences indicating that as yet unknown adhesins may play a role. However, despite some variations, the prevalence rate of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The autotrasporter Pic has been defined as a gene marker associated with spreading of infection to the urinary tract (40). Finally, comparison of EAEC isolates from HIV-positive and non-HIV diarrheal samples showed that HIV-positive isolates are stronger biofilm producers and more resistant to antibiotics than the non-HIV diarrheal isolates, which confirmed the heterogeneity of the EAEC isolates (42). …”
Section: Enteroaggregative E Coli (Eaec)mentioning
confidence: 57%
“…The autotrasporter Pic has been defined as a gene marker associated with spreading of infection to the urinary tract (40). Finally, comparison of EAEC isolates from HIV-positive and non-HIV diarrheal samples showed that HIV-positive isolates are stronger biofilm producers and more resistant to antibiotics than the non-HIV diarrheal isolates, which confirmed the heterogeneity of the EAEC isolates (42). …”
Section: Enteroaggregative E Coli (Eaec)mentioning
confidence: 57%